Предмет: Математика,
автор: dfgfgfdgfdg
Решить уравнение 0,2(y-3) - 1 = 0.5(y+3) - 0.4
Ответы
Автор ответа:
0
0,2y-0,6-1=0.5y+1,5-0,4
0,2-0,6-0,5+0,4=1,5+0,6+1
-0,5=3,1 /-0,5
y=-6,2
0,2-0,6-0,5+0,4=1,5+0,6+1
-0,5=3,1 /-0,5
y=-6,2
Автор ответа:
0
0,2(y-3) - 1 = 0.5(y+3) - 0.4
0.2y-0.6 - 1 = 0.5y + 1.5 - 0.4
0.2y -1.6 = 0.5y + 1.1
-0.3y = 2.7
y=-9
0.2y-0.6 - 1 = 0.5y + 1.5 - 0.4
0.2y -1.6 = 0.5y + 1.1
-0.3y = 2.7
y=-9
Похожие вопросы
Предмет: Литература,
автор: ko8artem
Предмет: Математика,
автор: MTE626
Предмет: География,
автор: feliksli813
Предмет: Математика,
автор: nastyapetrova04
Предмет: Алгебра,
автор: ненененен